Factors Influencing Farmers’ Interest in Using Trichoderma sp. for Chili Cultivation in Giritirto Village, Gunung Kidul - Mirani, Ira; Sukadi, Sukadi; Prayoga, Adi (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to identify and analyze the internal and external factors that influence farmers’ interest in using Trichoderma sp. as a biological control agent for chili cultivation in Giritirto Village, Purwosari Subdistrict, Gunung Kidul. Methodology: This study used a quantitative approach with purposive and random sampling methods. Data were collected through observation, interviews, questionnaires, and documentation. Instrument testing employed Microsoft Excel. Data analysis included validity and reliability tests, classical assumption tests, and multiple linear regression using SPSS software to assess the influence of various independent variables. Main Findings: The study found that farmers' interest in using Trichoderma sp. was generally high. Among the factors examined, the role of extension workers and the availability of facilities and infrastructure had a significant positive effect on farmers' interest. In contrast, age, education level, and farming experience did not have a significant influence on their interest in adopting Trichoderma sp.. Novelty/Originality of this study: This study uniquely explores the socio-demographic and institutional factors influencing farmers’ interest in adopting Trichoderma sp., which has rarely been addressed in previous research. It provides new insights into the human dimension of sustainable agriculture adoption, offering practical implications for policy and extension strategies to promote environmentally friendly farming practices.